MENGEKSPLORASI PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA DI FAKULTAS EKONOMI DAN BISNIS, UNIVERSITAS KRISTEN INDONESIA MALUKU - Silaya, Micrets Agustina (Jurnal Manajemen dan Profesional, 2024)
Financial responsibility is the process of managing money and other assets in a way that is considered productive. Money management (management finance) is also the process of managing finances effectively and efficiently. This study aims to examine the relationship between financial literacy and lifestyle on students' financial behavior and to determine the differences in financial literacy, lifestyle and financial behavior of students of the faculty of economics and business. This researcher is a quantitative researcher with a data collection technique using a questionnaire. The sample used was 100 students consisting of students of the faculty of economics and business, Universitas Kristen Indonesia Maluku (UKIM), this study used judgment sampling. The data analysis technique used the Classical Assumption Test, Multiple Linear Regression, t-test, f-test, and coefficient of determination. The results of this study are that the financial literacy variable does not affect the financial behavior of students of the faculty of economics and business UKIM. While the lifestyle variable affects the financial behavior of students of the faculty of economics and business UKIM.